EDUCATIONAL TRAVEL IN PROTESTANT FAMILIES FROM POST-RESTORATION IRELAND*. (29th October 2015) - Unknown
Abstract: This article examines travel within a group of Protestant families from Ireland over three generations after the Restoration. It offers both a case-study through which to reassess continental educational voyages, exploring a neglected period between the royalist exile of the 1650s and the mid-eighteenth-century heyday of the Grand Tour, and a contribution to current work on Irish elite formation. Histories of travel often begin as undifferentiated Englishmen or Britons arrive on the French or Dutch coast, but this study is the first to prioritize where travellers came from. Backgrounds, outlooks, and networks from home shaped experiences abroad. The article uses manuscript journals, letters, and financial accounts to locate travel within family educational strategies and to reconstruct preparations and advice. It explores how connections and identifications from home informed interactions with fellow travellers, expatriate communities, and foreign hosts. Travellers pursued two-sided interactions with hosts and destinations, returning with objects, accomplishments, and connections that fed into Irish elite formation. Continental links often feature in explanations of how Catholic Ireland survived, but this article shows that European encounters also contributed to Protestant hegemony. It demonstrates the importance of origins, as well as destinations, to understandings and experiences of educational travel.